2013
DOI: 10.1152/ajprenal.00337.2013
|View full text |Cite
|
Sign up to set email alerts
|

Gamma subunit second transmembrane domain contributes to epithelial sodium channel gating and amiloride block

Abstract: Shi S, Kleyman TR. Gamma subunit second transmembrane domain contributes to epithelial sodium channel gating and amiloride block. The epithelial sodium channel (ENaC) is comprised of three homologous subunits. Channels composed solely of ␣-and ␤-subunits (␣␤-channels) exhibit a very high open probability (P o) and reduced sensitivity to amiloride, in contrast to channels composed of ␣-and ␥-subunits or of all three subunits (i.e., ␣␥-and ␣␤␥-channels). A mutant channel comprised of ␣-and ␤-subunits, and a chi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 45 publications
(95 reference statements)
0
10
0
Order By: Relevance
“…a-Epithelial sodium channel but not b-and g-ENaC was involved in aldosterone-mediated regulation of Na þ balance in the kidneys [9]. Meanwhile, g-ENaC plays an important role for proper channel gating [28]. b-and g-Epithelial sodium channel could form a selective filter that accommodates Na þ and Li þ entry [29] and could interact with Nedd4, a ubiquitin-protein ligase that is involved in regulating ENaC function [30].…”
Section: Discussionmentioning
confidence: 99%
“…a-Epithelial sodium channel but not b-and g-ENaC was involved in aldosterone-mediated regulation of Na þ balance in the kidneys [9]. Meanwhile, g-ENaC plays an important role for proper channel gating [28]. b-and g-Epithelial sodium channel could form a selective filter that accommodates Na þ and Li þ entry [29] and could interact with Nedd4, a ubiquitin-protein ligase that is involved in regulating ENaC function [30].…”
Section: Discussionmentioning
confidence: 99%
“…ENaC regulation by Na+ self-inhibition (NaSI) enables the distal nephron to control Na + reabsorption based on fluctuating urinary Na + concentrations. Numerous studies have found that many of the human ENaC nonsynonymous single nucleotide variants affect channel function by altering the NaSI response [38][39][40][41][42].…”
Section: Mechanisms Of Enac Regulationmentioning
confidence: 99%
“…This response, referred to as Na + self-inhibition [2], provides a mechanism for cells in the distal nephron to rapidly tune the rate of Na + influx according to fluctuations of urinary [Na + ]. Numerous sites in the different domains of the extracellular regions of ENaC have been identified where amino acid substitutions alter channel activity, primarily by changing the Na + self-inhibition response [9,12,13,[16][17][18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%